The Role of Teachers as Coaches in Developing Students’ Numeracy Literacy Skils at SD Negeri Sambiroto Rembang - Astuti, Dwi Hajar Fitri; Haryati, Titik; Sumarno, Sumarno (FKIP - Universitas Riau, 2025)
Numeracy literacy is a fundamental competency in primary education, enabling students to apply mathematical concepts in daily life and to think critically in problem solving. However, many elementary school students still face challenges in achieving adequate proficiency. This study aims to examine the role of teachers as coaches in developing students’ numeracy literacy skills at SD Negeri Sambiroto, Rembang. Employing a qualitative case study design, data were gathered through classroom observations, in-depth interviews, and documentation, involving teachers, students, and school administrators. The findings indicate that teachers enact their coaching role through four interrelated strategies: creating a numeracy rich learning environment, facilitating contextual and meaningful instruction, designing structured and differentiated practice activities, and implementing formative and reflective assessments. These strategies form an integrated cycle that fosters active engagement, critical thinking, and the application of mathematics in authentic contexts. Teachers incorporate numeracy into daily routines, employ manipulative tools, adapt learning activities to varied student levels, and maintain learning portfolios to monitor progress. The study concludes that the teacher as coach model significantly enhances numeracy development, highlighting the importance of sustained teacher professional growth and strong leadership support in primary education.